2016
DOI: 10.17265/2159-581x/2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical and Mineralogical Evaluation of Soils Underlying a Failed Highway Section in South Eastern Nigeria

Abstract: Abstract:The Port Harcourt Enugu expressway is part of a national road grid that links parts of southern and northern Nigeria. The severe pavement failure between Umuahia and Okigwe section of the expressway covering a distance of about 30 km was investigated by geotechnical and mineralogical assessment of disturbed and undisturbed samples of the underlying soils. Also vertical electrical sounding was performed at the failed sections. Results indicate that the section is underlain by shales of the Imo Formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In investigating the potential reasons of road collapse of the Onitsha-Enugu expressway, Onuoha et al, (2014), collected and analyzed residual soil samples and concluded that the soils do not meet up with stipulated standards set by the Federal Ministry of Works and Housing. Tse and Efobo (2016) outlined potential causes for the frequent failure of the Port Harcourt -Enugu expressway to include utilization of substandard soils as the sub-grade, presence of shales of low permeability as well as the presence of signi cant amount of montmorillonite in the soil. Furthermore, Oyem et al (2020), Daramola et al (2018), identi ed poor drainage and high percentage nes and utilization of soils of high plasticity as some of the causative factors of road failure along the Sagamu-Papalanto highway in Southwestern Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…In investigating the potential reasons of road collapse of the Onitsha-Enugu expressway, Onuoha et al, (2014), collected and analyzed residual soil samples and concluded that the soils do not meet up with stipulated standards set by the Federal Ministry of Works and Housing. Tse and Efobo (2016) outlined potential causes for the frequent failure of the Port Harcourt -Enugu expressway to include utilization of substandard soils as the sub-grade, presence of shales of low permeability as well as the presence of signi cant amount of montmorillonite in the soil. Furthermore, Oyem et al (2020), Daramola et al (2018), identi ed poor drainage and high percentage nes and utilization of soils of high plasticity as some of the causative factors of road failure along the Sagamu-Papalanto highway in Southwestern Nigeria.…”
Section: Introductionmentioning
confidence: 99%